Selection of organic process and source indicator substances for the anthropogenically influenced water cycle. (April 2015) - Jekel, Martin; Dott, Wolfgang; Bergmann, Axel; Dünnbier, Uwe; Gnirß, Regina; Haist-Gulde, Brigitte; Hamscher, Gerd; Letzel, Marion; Licha, Tobias; Lyko, Sven; Miehe, Ulf; Sacher, Frank; et al.
Highlights: Proposal of individual micropollutants for assessment of anthropogenic influences. Source indicator substances for domestic wastewater, urban run-off and agriculture. Process indicator substances for natural and engineered processes. Abstract: An increasing number of organic micropollutants (OMP) is detected in anthropogenically influenced water cycles. Source control and effective natural and technical barriers are essential to maintain a high quality of drinking water resources under these circumstances. Based on the literature and our own research this study proposes a limited number of OMP that can serve as indicator substances for the major sources of OMP, such as wastewater treatment plants, agriculture and surface runoff. Furthermore functional indicators are proposed that allow assessment of the proper function of natural and technical barriers in the aquatic environment, namely conventional municipal wastewater treatment, advanced treatment (ozonation, activated carbon), bank filtration and soil aquifer treatment as well as self-purification in surface water. These indicator substances include the artificial sweetener acesulfame, the anti-inflammatory drug ibuprofen, the anticonvulsant carbamazepine, the corrosion inhibitor benzotriazole and the herbicide mecoprop among others. The chemical indicator substances are intended to support comparisons between watersheds and technical and natural processes independent of specific water cycles and to reduce efforts and costs of chemical analyses without losing essential information.